Punishment and Power in the Making of Modern Japan. - Botsman, Daniel V. (Princeton University Press, 2013)
The kinds of punishment used in a society have long been considered an important criterion in judging whether a society is civilized or barbaric, advanced or backward, modern or premodern. Focusing on Japan, and the dramatic revolution in punishments that occurred after the Meiji Restoration, Daniel Botsman asks how such distinctions have affected our understanding of the past and contributed, in turn, to the proliferation of new kinds of barbarity in the modern world. While there is no denying the ferocity of many of the penal practices in use during the Tokugawa period (1600-1868), this b.